القراءات الشاذة وموقفها عند المسلمين: دراسة قرآنية تحليلية = Abnormal readings and attitudes towards Muslims: an analytical qur'anic study - Yaacob, Solehah@Nik Najah Fadilah; Awang Ali, Mohammad Amnan (Scientific institute of advanced Training, 2015)
تهدف المقالة إلى توثيق بعض النصوص القرآنية متواترةً أم شاذةً. وإلى جانب ذلك، تركز هذه المقالة على أشهر القراء الذين نُسِب إليهم بهاتين القراءتين (متواترةً وشاذةً). ومفهوم من ذلك، أن القراءات الشاذة تختلف عن القراءات المتواترة لأنها تفتقد شروط المطلوبة في المتواترة. ومن خلال هذه الدراسة يعد البحث بالإجابة عن بعض الأسئلة التي تدور في أذهان بعض الدارسين؛ ما هي العلاقة بين القراءات الشاذة والمتواترة؟ وما هو المقياس لهاتين القراءتين؟ وما هي شروط القراءات المتواترة؟ وهل القراءة الشاذة خارجة عن القراءة السبعة والعشرة؟ وهل تجوز في الصلاة بالقراءات الشاذة؟ وهل نحتاج إلى القراءات الشاذة؟ وهل نستطيع الاحتجاج بالقراءات الشاذة؟ وما هي فوائدها؟ لإجابة هذه الأسئلة والتساؤلات وذلك بعرض الشواهد والبراهين وأقوال العلماء، متبعة في ذلك المنهج القرآني التحليلي. ******************************************************************************* The article aims at documenting some of the Qur'anic texts that are frequent or irregular. In addition, this article focuses on the most popular readers attributed to these readings (frequent and abnormal). The concept of this is that the abnormal readings differ from the frequent readings because they lack the conditions required in the frequent. Through this study, the research is to answer some of the questions that are in the minds of some scholars; what is the relationship between abnormal readings and frequent? What is the measure of these readings? What are the conditions for frequent readings? Is abnormal reading beyond the seven and ten reading? Is it permissible to pray with anomalous readings in prayer? Do we need anomalous readings? Can we invoke abnormal readings? What are their benefits? To answer these questions and questions by presenting the evidence and proofs and statements of scientists, followed by the Koranic analytical approach.